The Effect of Using Hand Puppet Media on Learning Outcomes of Listening to Fairy Tales for Class II Students of SDN 88 Lonrong, Soppeng Regency - Rizal Agustira Rasyid; Widya Hastuti (JED (Jurnal Etika Demokrasi), 2021)
The main problem in this study is that there are still many students who score below the KKM, this was found by the researchers when conducting initial observations in Class II SDN 88 Lonrong on the Indonesian subject of listening to fairy tales. So, this study aims to improve learning outcomes of listening to fairy tales for Class II students of SD Negeri 88 Lonrong, Soppeng Regency by using hand puppet media in ix during the teaching and learning process. This type of research is pre-experimental research with a one group pre-test-post-test model that only involves one class. The purpose of this study was to determine student learning outcomes by using hand puppet media in second grade students of SD Negeri 88 Lonrong, Soppeng Regency. The sample in this study was class II students, totaling 15 people. The study was carried out for 5 meetings with an interval of 2 months. The results showed that in the pretest activity (without using media), there were 11 students or 73% who were in the incomplete category and 4 students or 27% who experienced completeness. The average learning outcomes obtained by students during the pretest only reached 57.33. Classically, it has not met the minimum completeness criteria (KKM). While in the posttest activity using hand puppet media, there were 14 students who scored above the KKM with an average score of 83.33. This indicates that there is an increase in learning outcomes after being given treatment. So, it can be concluded that the use of hand puppet media has a significant influence on the learning outcomes of listening to fairy tales for the Grade II students of SD Negeri 88 Lonrong, Soppeng Regency.Masalah utama dalam penelitian ini adalah masih banyaknya siswa yang memperoleh nilai di bawah KKM, hal ini ditemukan peneliti saat melakukan observasi awal di Kelas II SDN 88 Lonrong pada mata pelajaran Bahasa Indonesia materi menyimak dongeng. Sehingga penelitian ini bertujuan untuk meningkatkan hasil belajar menyimak dongeng siswa Kelas II SD Negeri 88 Lonrong Kabupaten Soppeng dengan menggunakan media boneka tangan pada ix saat proses belajar mengajar berlangsung. Jenis penelitian ini adalah penelitian pra-eksperimen dengan model one group pre test-post test yaitu hanya melibatkan satu kelas. Tujuan penelitian ini untuk mengetahui hasil belajar siswa dengan menggunakan media boneka tangan pada Siswa Kelas II SD Negeri 88 Lonrong Kabupaten Soppeng. Sampel dalam penelitian ini adalah siswa kelas II yang berjumlah 15 orang. Penelitian dilaksanakan selama 5 kali pertemuan dengan interval waktu 2 bulan. Hasil penelitian menunjukkan bahwa pada kegiatan pretest (tanpa menggunakan media), terdapat 11 siswa atau sebesar 73 % yang berada pada kategori tidak tuntas dan 4 orang siswa atau 27 % yang mengalami ketuntasan. Adapun rata-rata hasil belajar yang diperoleh siswa saat pretest hanya mencapai 57,33. Secara klasikal belum memenuhi kriteria ketuntasan minimal (KKM). Sedangkan pada kegiatan posttest dengan menggunakan media boneka tangan, terdapat 14 orang siswa yang memperoleh nilai di atas KKM dengan ratarata nilai 83,33. Hal ini menandakan bahwa terdapat peningkatan hasil belajar setelah diberikan perlakuan (treatment). Sehingga dapat disimpulkan bahwa penggunaan media boneka tangan memberikan pengaruh signifikan terhadap hasil belajar menyimak dongeng siswa Kelas II SD Negeri 88 Lonrong Kabupaten Soppeng.